The Effect of Operating Costs, Trade Payables & Sales on Net Income in the Food & Beverage Company Sector Listed on the Indonesian Stock Exchange for the Period 2015-2018 - Yeni Ariesa; Della Della; Panny Fransiska; Sonia Falensia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This research was conducted to test and analyze the relationship between operating costs, accounts payable and sales to net income in the Food & Beverage sector listed on the Indonesia Stock Exchange for the 2015-2018 period. This type of research is quantitative research with a deductive approach and descriptive research characteristics. The total population of 18 companies with purposive sampling technique obtained a sample of 12 companies. The data analysis technique used multiple linear regression. The test results show that operating costs, accounts payable and sales have an effect on net income. The partial test results are operating costs and sales have a positive effect on net income and trade payables have a negative effect on net income. Based on the test of the coefficient of determination, it can be seen that the influence of the variables used in explaining the dependent variable is 83.6%, the rest is influenced by other variables of 16.4%.